The Responsibility of the Directorate General of Intellectual Property in Resolving the Trademark Dispute Over 'Tempo Gelato' - Belliana Herlina; Christine Kansil (Journal of Law, Politic and Humanities, 2024)
The Law Number 20 of 2016 concerning Trademarks and Geographical Indications aims to provide clear legal protection for legitimate trademark owners. A legitimate trademark owner is the person who first registers their trademark or service mark. In practice, conflicts often arise due to unilateral trademark registrations. This study focuses on the trademark dispute case of Tempo Gelato, where one party in a business partnership registered the trademark without the consent of the original owner. The Directorate General of Intellectual Property Ministry of Law and Human Rights Republic of Indonesia plays a crucial role in preventing unilateral registrations and ensuring that dispute resolution processes adhere to legal provisions. This study also examines the responsibilities of government agencies in cases of unilateral registration, including the dispute resolution mechanisms offered in the law and their vital role in safeguarding the exclusive rights of trademark owners to prevent abuse of the registration system.